SOME PROBLEMS OF A JUDICIAL PRACTICE IN THE CASES ON ESTABLISHING THE FACT OF LABOUR RELATIONS - Vyshnovetska, Svitlana; Kyrychenko, Viktoriia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to analyse a judicial practice in the cases on establishing the fact of labour relations in order to separate the problematic aspects in this field and to avoid in further the disputes on establishing the fact of labour relations. Research methods: documentary analysis and synthesis, comparative analysis, cognitive and analytical, as well as methods of systematization and generalization. By hermeneutic approach, the authors analysed a mechanism of application of general legal prescriptions by the courts to a specific situation. Results: the criteria used by judicial practice to qualify the relations as labour ones have been clarified. Discussion: a necessity to consolidate the features of labour relations at the level of a code is substantiated in order to form the fixed judicial practice in cases on establishing the fact of labour relations, ensuring its unity. Based on a judicial practice analysis, the authors concluded that a judicial practice is not fixed in the cases on establishing the fact of labour relations. Therefore, establishing the fact of labour relations, a legal evaluation should be given both to the agreements themselves, and to the content and legal nature of the relations that arise between the parties, their features. The most common feature used by a judicial practice is the characterization of work as a process, not as a result. At the same time, in the conditions of modern challenges and the spread of remote work, the ability of a remote worker to work not “for the process” but “for the result” becomes a key one. Performing the result-oriented work by the employee becomes a priority. And this should be taken into account both by the legislator determining the features of modern labour relations, and by judicial authorities qualifying such relations. The authors note that the application of the criterion of control by the employer to determine the legal nature of the relations between the parties is not as widespread in a judicial practice of Ukraine as in a judicial practice of the United States. At the same time, this criterion acquires a new content, since control shifts from the area of monitoring the employee to the area of planning the tasks that the employee should perform in a certain period of time. It was concluded that the difficulty of establishing the fact of labour relations is also related to the fact that work regulated by the labour law is increasingly moving to the service sector, which is characterized by the independence of the person performing the work, as well as the orientation to the result.